PERAN HUKUM ISLAM DALAM HARMONISASI HAK DAN KEWAJIBAN ASASI MANUSIA DALAM PERSPEKTIF PANCASILA - Paramitha, Vallencia Nandya (LPPM STAI Muhammadiyah Probolinggo, 2024)
In principle, Human Rights (HAM) are a basic right that is inherent in every human being because these rights are not a gift from a person, organization or state but are an invaluable gift from Allah SWT, but are priceless from Allah SWT. The concept of harmonization of Islamic law in realizing the implementation of human rights and obligations from a Pancasila perspective can bring good benefits to Indonesian society amidst the sensitivity of the problems occurring in Indonesia. This research examines the concept of human rights from Western and Islamic views and the role of Islamic law in realizing harmonization of human rights and obligations from the Pancasila perspective. This writing uses a type of normative research which is carried out by searching the literature which is then supported by additional data to strengthen this research. Using this normative research method will also help answer the concept of human rights according to Islamic law and the role of Islamic law in realizing harmonization of human rights and obligations from the Pancasila perspective. Results: It is important to remember that Islamic law and human rights cannot be separated absolutely. In Pancasila Law, these two concepts complement each other and must not conflict with each other. This is also in line with Islamic teachings which emphasize the importance of justice and balance in various aspects of life. This principle is in accordance with the teachings of the Islamic religion which emphasizes the importance of justice and equality in society. So, Islamic Law and Human Rights in Pancasila Law have the same goal, namely creating a just and equitable society. The conclusion of this writing is that the relationship between Islamic law and human rights in Pancasila Law is a complementary relationship and cannot be separated. Both have an important role in creating an Indonesian society based on Pancasila, so we must understand and appreciate these two concepts in order to live in harmony and balance in accordance with the nation's noble values.